2020
DOI: 10.1016/j.psychres.2020.113339
|View full text |Cite
|
Sign up to set email alerts
|

Associations of moderate to vigorous physical activity and sedentary behavior with depressive and anxiety symptoms in self-isolating people during the COVID-19 pandemic: A cross-sectional survey in Brazil

Abstract: Highlights Nearly half of the participants spent more than 30 min per day in moderate to vigorous physical activity (MVPA). One-third of the participants spent more than 10 h per day sitting. Those reporting over 30 min of MVPA/day were less likely to present depressive, anxiety, or co-occurring depressive and anxiety symptoms. Those reporting over 10 h sitting/day were more likely to present depressive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
197
1
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(253 citation statements)
references
References 30 publications
30
197
1
25
Order By: Relevance
“…Four studies had a prospective longitudinal design [26,29,39,36], one was a cross-sectional study with a retrospective measure of the exposure factor (henceforth treated as retrospective) [5], and 16 were crosssectional studies [9, 23-25, 27, 29-35, 37, 6, 38, 40, 28, 41]. A total of 7 studies were conducted in Asia [24,25,27,30,33,39,40], 6 in Europe [9,26,31,32,35,36], 3 in South America [28,29,6], 3 in North America [23,34,5], one in Oceania [38] and one study included a multinational sample [37].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies had a prospective longitudinal design [26,29,39,36], one was a cross-sectional study with a retrospective measure of the exposure factor (henceforth treated as retrospective) [5], and 16 were crosssectional studies [9, 23-25, 27, 29-35, 37, 6, 38, 40, 28, 41]. A total of 7 studies were conducted in Asia [24,25,27,30,33,39,40], 6 in Europe [9,26,31,32,35,36], 3 in South America [28,29,6], 3 in North America [23,34,5], one in Oceania [38] and one study included a multinational sample [37].…”
Section: Resultsmentioning
confidence: 99%
“…3 out of 5 studies reported higher frequencies of PA to be signi cantly associated with less depression [27,29,36] and 2 out of 4 studies to be signi cantly associated with less anxiety [27,29]. One study showed that vigorous but not moderate PA is signi cantly associated with less depression and anxiety symptoms [6] and another study indicated that light and vigorous PA is signi cantly correlated with less depression, but moderate intensity was not [23]. Out of 5 studies assessing an association between regular and guideline-consistent PA less depression and anxiety symptoms, two studies demonstrate that regular PA (compared to not regular) is signi cantly associated with less depression and anxiety symptoms [27,30] and 1 study demonstrated that guideline conforming moderate to vigorous PA is associated with lower odds of depression and anxiety [6].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Mental health was also shown to be negatively impacted by COVID-19-related confinement leading to increased stress anxiety and depression symptoms. [23][24][25][26] Studies have shown that lockdown is a great stress for citizens; thus, the characteristics of exercise selection may be affected by such a stress. A previous review has concluded a differential impact for stress on exercise adoption, maintenance, and relapse, where habitually active individuals exercise more in the face of stress, and those in beginning stages exercise less.…”
Section: Discussionmentioning
confidence: 99%